Growth of a Capsid Mutant of Bacteriophage φX174 in a Temperature-Sensitive Strain of Escherichia coli - Vito, Christine C. (1975)
A capsid mutant of φX174 is capable of forming replicative form and synthesizing single strands at the restrictive temperature in a dnaB mutant of Escherichia coli. Under similar conditions, the wild-type bacteriophage is incapable of either step in viral synthesis.